Weed Management in Cocoa Nursery - Shylaja P V (Department of Agronomy, College of Horticulture, 2001)
Experiments were conducted during 2000-2001 at the College of Horticulture, Kerala Agricultural University, Thrissur with the objective of suggesting appropriate weed management strategies involving solarization, fumigation, biofertilizers and herbicides for cocoa nursery. The investigation consisted of two experiments. In the first experiment, solarization at different intervals (15, 30 and 45 day) and fumigation were compared together with biofertilizers (Azospirillum, V AM, Azospirillum + V AM). Seven pre-emergence herbicides were screened in the second experiment along with weed free and untreated control. The major weeds of the nursery area were broad leaf weeds. Solarization for 30 and 45 days and fumigation were very effective in controlling weed growth and biomass of weeds. The temperature at 5 cm depth was 7-9.5°C more than the non-solarized soil. Solarization for 30 and 45 days and fumigation reduced the population of fungi, bacteria and actinomycetes considerably. Increases in the availability of some nutrients - available P, exchangeable K, Ca and Mg - were also observed as a result of solarization for 30 and 45 days. Organic carbon, total nitrogen, ammoniacal nitrogen, nitrate nitrogen were unaffected. Biofertilizers seems to have no appreciable effect on weed population and growth. ,. Solarization for 30 and 45 days and fumigation increased the growth of cocoa seedlings. Increased growth of seedlings resulted in early selection of seedlings for budding from this treatments. Biofertilizers also had significant influences on growth parameters of cocoa and earliness in attaining collar girth of buddable size. Certain growth characters showed interaction effects between